Is legal status associated with mental illness among newly arrived refugees in Sweden: an epidemiological study - Sara Delilovic; Ana Hagström; Jad Shedrawy; Anna Clara Hollander; Knut Lönnroth; Henna Hasson (BMC Psychiatry, 2023)
Abstract Background There are about 80 million forcibly displaced people globally. Migrants are at heightened risk for mental illness compared to host country populations. While previous research highlights the need to adequately assess mental illness, few have taken the diversity among newly arrived migrants into account. This study aims to estimate the prevalence and associated risk factors of mental illness among asylum seekers, quota and other refugees in Stockholm, Sweden. Methods Using a cross-sectional design, data was collected as part of a mental health screening initiative integrated into routine health examinations in two health care clinics in Stockholm. Screening was done with the Refugee Health Screener, RHS-13, a validated instrument for assessing mental health in refugee populations. Results A total of 1163 individuals were eligible for screening, of whom 566 participated (response rate 48.6%). Among the participants, 47.9% indicated symptoms of mental illness. Compared with asylum seekers, the risk of mental illness was lower among quota and other refugees (adjusted odds ratio 0.60, 95% confidence interval 0.37-1.00). Female sex, higher age, coming from a middle-income country and low probability of being granted asylum were significant predictors of mental illness. Conclusion Refugee legal status is associated with mental illness. Asylum seekers are at greater risk of mental illness compared to quota and other refugees. Our findings call for screening for mental illness among newly arrived migrants, especially among those with pending residence permits.